A dPIP5K Dependent Pool of Phosphatidylinositol 4,5 Bisphosphate (PIP2) Is Required for G-Protein Coupled Signal Transduction in Drosophila Photoreceptors. - Chakrabarti, P.; Kolay, S.; Yadav, S.; Kumari, K.; Nair, A.; Trivedi, D.; Raghu, P. (PLoS Genetics, 2015)
Multiple PIP2 dependent molecular processes including receptor activated phospholipase C activity occur at the neuronal plasma membranes, yet levels of this lipid at the plasma membrane are remarkably stable. Although the existence of unique pools of PIP2 supporting these events has been proposed, the mechanism by which they are generated is unclear. In Drosophila photoreceptors, the hydrolysis of PIP2 by G-protein coupled phospholipase C activity is essential for sensory transduction of photons. We identify dPIP5K as an enzyme essential for PIP2 re-synthesis in photoreceptors. Loss of dPIP5K causes profound defects in the electrical response to light and light-induced PIP2 dynamics at the photoreceptor membrane. Overexpression of dPIP5K was able to accelerate the rate of PIP2 synthesis following light induced PIP2 depletion. Other PIP2 dependent processes such as endocytosis and cytoskeletal function were unaffected in photoreceptors lacking dPIP5K function. These results provide evidence for the existence of a unique dPIP5K dependent pool of PIP2 required for normal Drosophila phototransduction. Our results define the existence of multiple pools of PIP2 in photoreceptors generated by distinct lipid kinases and supporting specific molecular processes at neuronal membranes.